High rates of reinfection and incidence of bacterial sexually transmitted infections in a cohort of female sex workers from two Indian cities: need for different STI control strategies?. Issue 1 (29th November 2012) - Das, Anjana; Pathni, Anupam Khungar; Narayanan, Prakash; George, Bitra; Morineau, Guy; Saidel, Tobi; Prabhakar, Parimi; Deshpande, Gururaj Rao; Gangakhedkar, Raman; Mehendale, Sanjay; Risbud, Arun
Abstract : Background: Female sex workers (FSWs) in India are provided a standardised package of clinical interventions for management of sexually transmitted infections (STIs). A study was conducted among FSWs at known high STI prevalence sites to determine the effectiveness of the service package. Methods: A cohort of FSW clinic attendees in two cities, Hyderabad and Mumbai, were enrolled and followed up from October 2008 to November 2009. At each visit, behavioural and clinical data were obtained and vaginal swabs collected for laboratory testing of cervical infections (gonorrhoea and chlamydia). Results: 417 participants were enrolled, of whom 360 attended at least a follow-up visit. Prevalence of cervical infections did not change between the baseline and final visits (27.7% and 21.3% respectively, p=0.08) in spite of presumptive treatment at baseline and syndromic management at all visits. The proportion of asymptomatic cervical infections increased from 36% at baseline to 77% at the final visit. Incidence rate of cervical infections was high (85.6/100 person years) and associated with a prevalent cervical infection at baseline (HR=2.7, p<0.001) and inconsistent condom use with non-commercial partners (HR=2.5, p=0.014). Conclusions: High rates of STIs persisted despite the interventions due to poor condom use, minimal partner treatment, and high prevalence and incidence of STIs with a large proportion of asymptomatic infections. High-prevalence FSW sites in India need to design more effective partner treatment strategies and consider increasing the frequency of presumptive treatment as a temporary measure for quickly reducing STI prevalence, with renewed emphasis on consistent condom use with all partners.